การศึกษาความต้องการมีส่วนร่วมของชุมชนในการดำเนินงานของโรงเรียนขยายโอกาสทางการศึกษากลุ่มเครือข่ายแม่ปิงบรรพต อำเภอบรรพตพิสัย สำนักงานเขตพื้นที่การศึกษาประถมศึกษานครสวรรค์ เขต 2 - เลิศจำนงจิตร์, ณัฐพัชร์; น้อยจันทร์, นันทิยา (Ganesha Journal, 2012)
[บทคัดย่อภาษาไทยไม่สมบูรณ์] This research aimed at studying community participation in educational expansion school management of Mae Ping Banphot Educational Network, Banphotphisai District, Nakhonsawan Educational Service Area 2. The 99 subjects under the study comprised 24 school boards (excluding those who were administrators by position), 49 parents, 4 community leaders, 3 religious leaders, and 19 community organization representatives, Purposive sampling and drawing lots were also used. The tool employed in the study was a 5-point rating scale questionnaire with the reliability coefficient of 0.96. The statistics used for data analysis were percentage, mean, and standard deviation. This research can be concluded as follows : 1. For academic aspect, the needs for participation of the community in the service area of the educational expansion school management of Mae Ping Banphot Educational Network were in acknowledging the policy and content of core courses, the guidelines in learning and instruction arrangement, and in presenting information, problems, and community needs conducive to local curriculum development in accordance with the condition of the community. 2. For budgeting aspect, the needs for participation of the community in the service area of the educational expansion school management of Mae Ping Banphot Educational Network was in arranging activities to mobilize resources and budget to support educational management of the school. 3. For general administration, the needs for participation of the community in the service area of the educational expansion school management of Mae Ping Banphot Educational Network was in acknowledging the yearly annual report of the school. 4. For personnel aspect, the needs for participation of the community in the service area of the educational expansion school management of Mae Ping Banphot Educational Network was in taking part in personnel administration and management of the school.